High Sensitivity Polyurethane‐Based Fiber Strain Sensor with Porous Structure via Incorporation of Bacterial Cellulose Nanofibers. (15th March 2021) - Sheng, Nan; Ji, Peng; Zhang, Minghao; Wu, Zhuotong; Liang, Qianqian; Chen, Shiyan; Wang, Huaping
Abstract: With the rise of wearable devices, flexible sensors have received extensive attention and research due to their great potential in human health detection and joint motion. Here, a flexible fiber strain sensor is directly obtained by a common wet‐spinning method, which used thermoplastic polyurethane as the elastomer, carbon nanotubes, and graphene as conductive fillers by incorporating 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl oxidized bacterial cellulose nanofibers (BCN) as the dispersant and binding agent. The introduction of BCN can effectively improve the interaction between the polymer matrix and the conductive fillers, and bear a part of the tensile stress and the supporting force during the fiber formation, to form the porous structure, which can efficiently carry and transfer the tensile force. Under the synergistic effect of various components, the fiber strain sensor with wide response range (230%), high gauge factor values of 17.8 (0−70%), 326.6 (70−150%), and 1501.0 (150−230%), fast response time, and recovery time (≈100 ms), and long‐term cyclic stability (>10 000 cycles) are prepared. In the fiber sensor, the ideal combination of excellent strain sensing performance and flexible wearable characteristics has been realized which will be of great significance in the field of weaving, lightweight, and foldable electronic devices. Abstract : The present work prepares a flexible TPU‐based fiber strain sensor. The introduction of BCN nanofibers effectively improves the interaction between the polymer matrix and the conductive fillers. They have high sensitivity, a wide response range (230%), fast response and recovery time (100 ms), and long‐term cyclic stability (>10 000 cycles), which have great advantages in the detection of human motion.